Determinan Pemeriksaan Payudara Sendiri Sebulan Sekali secara Teratur pada Wanita Usia Subur - Ari Pertama Watiningsih; Desak Ketut Sugiartini (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Awareness of breast cancer prevention methods is very important in reducing morbidity and mortality caused by breast cancer. One of them is by breast self-examination (BSE) because it is easy, cheap, privacy, safe and does not require special equipment. In fact this method has not been widely applied by most women. The purpose of this study was to determine the determinants of the implementation of breast self-examination once a month on a regular basis by women of childbearing age in the Kubutambah District. The method of research was observational with a cross sectional approach. The population in this study is all women of childbearing age in the Kubutambah District. Samples were taken by purposive sampling with a large number of samples determined as many as 154 respondents. Data collection using a questionnaire. Researchers filled out the questionnaire with structured interview techniques and assisted respondents. The study began in June-September 2019. After the data were collected, an univariate analysis was performed with a frequency distribution test, bivariate with the Spearman Rank test and multivariate with a Logistic Regression test using software. The results of this study found that the variables that were determinants of breast self-examination every month were the level of education (OR = 5,321.95% CI: -0.324--0.213), mass media access (OR = 3,543.95% CI: -0.213-- 0.124), spouse / family support (OR = 7,002.95% CI: -1.342--0.543) and peer age group support (OR = 5,326.95% CI: -3.234--1.342) still jointly influence the examination breast once a month regularly.